EVALUATION OF DISORDERS FEATURES OF THE INTRACARDIAC HEMODYNAMICS AND FUNCTIONAL STATE OF MYOCARDIUM IN WOMEN WITH ARTERIAL HYPERTENSION DEPENDING ON THE PRESENCE OF CONCOMITANT IRON DEFICIENCY ANEMIA, ITS SEVERITY AND DURATION - Сулим, С.О. (World of Medicine and Biology, 2016)
One hundred and forty one women, aged 54-87 years old with arterial hypertension of stage II, with and without concomitant iron deficiency anemia were examined. Disorders’ features of intracardial hemodynamics and functional state of the myocardium depending on the presence of concomitant iron deficiency anemia, its severity and duration were studied in the following patients with the help of echocardiographic research. It was discovered that circulatory compensation in women with low concomitant iron deficiency anemia happens only due to the formation of the central hemocirculation hyperkinetic type. In turn, mild concomitant iron deficiency anemia associates with more severe hemodynamic changes: availability of dilatation instrumental signs and volume overload of right and left heart chambers; more severe LV structural remodeling and increasing frequency of eccentric hypertrophy registration. Signs of more substantial disorders of LV functional state and significantly higher frequency of registration of eccentric left ventricular hypertrophy should be underlined as specific functional markers of lasting iron deficiency anemia in women with arterial hypertension.
Keywords: hypertension; iron deficiency anemia; intracardiac hemodynamic; functional state of the myocardium